The involvement of family in child protection cases in Iceland (Journal of Comparative Social Work, 2015)
The aim of this study is to examine the involvement of families in child protection cases in Iceland, as well as to shed light on the attitudes of child protection workers on the importance of including families while working on child protection cases. The study is part of an international comparative analysis called: Social Work with Families: Social Workers’ Constructions of Family in Professional Practice. This article only addresses the Icelandic segment of the research. In the study, qualitative methods were used and three focus groups were conducted, in which the same three-step vignette about a child protection case was presented. The findings highlighted how difficult child protection workers found it to define the family. The main element is that family are those individuals closest to the child and connected to them through emotional ties, as Icelandic child protection workers seem to strive to involve family in child protection cases. However, there are signs which show that when working with more complicated cases the definition of a family becomes narrower, and involvement is restricted mostly to parents and grandparents. The findings also show that attitudes toward fathers differ from those toward mothers. The mother is expected to support and create security for the child, while the father is judged mostly on his violent behaviour and is not automatically regarded as providing support or actively taking responsibility for his child.